Aufklärungsdiskurse in der deutschsprachigen Regionalpresse Zentraleuropas, 1800-1920 / L'héritage des Lumières dans la presse de langue allemande en Europe centrale, 1800-1920 - Nicklas, Thomas; Birk, Matjaž (Studia Habsburgica, 2022)
The contributions brought together in this volume deal with German-language newspapers in Central Europe in the ""long 19th century"" from the perspective of the continuing influence of Enlightenment ideas in the regional press of the Habsburg Monarchy. Outstanding experts analyse the transfer of Enlightenment concepts in the Central European press. At the same time, the question is raised as to whether these regions had their own ideas of Enlightenment. The essays contained here in German are accompanied by French and English summaries.